2017
DOI: 10.1080/21505594.2017.1343769
|View full text |Cite
|
Sign up to set email alerts
|

Suppressive effect of dengue virus envelope protein domain III on megakaryopoiesis

Abstract: Dengue virus (DENV) infection can cause severe, life-threatening events, and no specific treatments of DENV infection are currently approved. Although thrombocytopenia is frequently observed in dengue patients, its pathogenesis is still not fully understood. Previous studies have suggested that DENV-induced thrombocytopenia occurs through viral-replication-mediated megakaryopoiesis inhibition in the bone marrow; however, the exact mechanism for megakaryopoiesis suppression remains elusive. In this study, a red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 50 publications
(74 reference statements)
0
41
0
Order By: Relevance
“…In the current study, Lin et al (2017) suggest that DENV-envelope protein domain III (DENV-EIII) is sufficient to suppress differentiation of megakaryocytes to thrombocytes and that replication within haematopoietic precursors is not required. 12 The investigators hypothesized that engagement of DENV-EIII with the cell surface would be sufficient to perturb cell signaling and the differentiation of the thrombocyte progenitors. 12 Previous research has shown that DENV antigens are present on the surface of thrombocytes and that virions can enter into these cells through engagement with DC-SIGN.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…In the current study, Lin et al (2017) suggest that DENV-envelope protein domain III (DENV-EIII) is sufficient to suppress differentiation of megakaryocytes to thrombocytes and that replication within haematopoietic precursors is not required. 12 The investigators hypothesized that engagement of DENV-EIII with the cell surface would be sufficient to perturb cell signaling and the differentiation of the thrombocyte progenitors. 12 Previous research has shown that DENV antigens are present on the surface of thrombocytes and that virions can enter into these cells through engagement with DC-SIGN.…”
mentioning
confidence: 99%
“…12 The investigators hypothesized that engagement of DENV-EIII with the cell surface would be sufficient to perturb cell signaling and the differentiation of the thrombocyte progenitors. 12 Previous research has shown that DENV antigens are present on the surface of thrombocytes and that virions can enter into these cells through engagement with DC-SIGN. 4,9 To test their hypothesis, the investigators confirmed that DENV-EIII could bind to megakaryocytes, and then administered DENV-EIII to a mouse model and progenitor cells from both murine bone marrow and human cord blood.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…1B) of polyclonal anti-NS1 Igs induce cell death of lymphoid cell lines, we used affinity-enriched fractions of the anti-NS1 Ig (anti-NS1-TACI Ig and anti-NS1-DR4 Ig) plus additional proteins [e.g. recombinant glutathione S-transferase (rGST; a negative control protein 23,30,31 ), recombinant NS1 (rNS1), recombinant TACI (rTACI) and recombinant DR4 (rDR4)] to perform neutralization experiments. Data indicated that anti-NS1-DR4 and anti-NS1-TACI Ig treatments induced cell death of Raji and Jurkat cells in a dose dependent manner (Suppl.…”
Section: Anti-taci and Anti-dr4 Antibodies Induced Cell Death In Lympmentioning
confidence: 99%